Synthesis, characterization, and structural properties of intracellular copolyester poly(3-hydroxybutyrate-co-3-hydroxyvalerate) produced by Comamonas sp. EB 172 from renewable resource - Mumtaz, Tabassum; Abd. Aziz, Suraini; Phang, Lai Yee; Wan Yunus, Wan Md. Zin; Shirai, Yoshihito; Hassan, Mohd Ali (Taylor & Francis, 2010)
Microbial copolymer was produced by a local isolate, Comamonas sp. EB 172, using mixed organic acids such as acetic, propionic, and butyric acids as carbon sources in pH-stat fed-batch fermentation. Maximum polymer production (6.59 g/L) was achieved at 50 h of fermentation when 73.64 g/L mixed acids, generated from the acidogenic fermentation of palm oil mill wastewater, were used. Accumulation of polymer in the cell was 70% (wt/wt), which was observed under transmission electron microscope. The morphological, chemical, thermal, and mechanical properties of the solvent-extracted biopolymer were determined by various techniques (SEM, GC, 13C NMR, FT-IR, TGA, and tensile testing). The copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) consisted of 87 mol% β-hydroxybutyric acid (HB) and 13 mol% β-hydroxyvaleric acid (HV). With chemical properties similar to commercial PHBV and mechanical strength of around 30 MPa and 8% elongation at break, the biopolymer offers potential for industrial applications.